CHARLES DICKENS' PROSE: SYNTACTIC DEVICES OF REPETITION, EXCLAMATIONS AND RHETORICAL QUESTIONS: https://doi.org/10.5281/zenodo.17250264 - Abdurazzoqova , Kamola; Chekulay , Igor (International scientific and practical conference, 2025)
This article explores the syntactic devices of repetition, exclamations, and rhetorical questions in the prose of Charles Dickens, emphasizing their structural, stylistic, and emotional functions. Repetition—manifested through anaphora, epiphora, parallelism, and combined forms—creates rhythm, reinforces motifs, and heightens expressive intensity. Exclamations contribute immediacy and emotional force, shaping tone and character voice. Rhetorical questions, in turn, engage readers, convey irony or indignation, and highlight social criticism. The interplay of these devices demonstrates Dickens’ syntactic mastery, enabling him to blend rhetorical sophistication with deep emotional resonance. The study reveals how these techniques shaped Dickens’ unique narrative style and contributed to his lasting impact on English prose.